The Politics and Pedagogy of Nationalism: Authentic Learning on Identity and Conflict. (22nd December 2021) - Gilbert, Danielle
Abstract: In recent decades, nationalism has emerged from the distant purview of history to become the primary driver of some of the world's biggest news. Given the prominence of nationalist conflict, students in political science increasingly study the subject with modern references in mind. This article describes the design for a timely undergraduate political science course on the causes and consequences of nationalism, with a focus on four central learning objectives: understanding theories and concepts in the study of nations and nationalism; applying theories to contemporary events; exploring issues of identity among a community of learners; and developing analytical and professional skills. I describe in detail two course assignments that exemplify these pedagogical objectives. In the "nationalism in the news" assignment, students give an in-class oral presentation on a current news story, interpreting the event through the lens of course themes. In the "national anthems analysis" paper, students analyze the lyrics of the national anthem of their choosing, linking symbols to interpretations of different nationalism types. I conclude by offering suggestions for adapting these and other course assignments to a range of classrooms and students.